"Arcus retinalis": A novel clinical marker of sub-internal limiting membrane hemorrhage. Issue 4 (July 2021) - Kumar, Vinod; Goel, Neha
Introduction: Preretinal hemorrhages can be located in subhyaloid or sub-internal limiting membrane (ILM) space. Though optical coherence tomography (OCT) may help to distinguish the exact location of hemorrhage in selected cases, it is often difficult to discern clinically. The purpose is to describe a novel clinical sign named "arcus retinalis" as a clinical marker of sub-ILM hemorrhage. Methods: Retrospective observational case series. Ophthalmic records of 31 eyes with sub-ILM hemorrhage were analyzed. The sub-ILM nature of the hemorrhage was confirmed either by the presence of two distinct layers (ILM and posterior hyaloid) on OCT or on intraoperative sub-ILM localization of the hemorrhage during vitrectomy. Results: 15 out of 31 eyes with sub-ILM hemorrhage demonstrated a retinal yellowish-white arc corresponding to the outer margin of the sub-ILM hemorrhage. A complete circle was not seen in most of the cases. This arc corresponded to a vertical peg-like structure in the outer retina on OCT and had a tendency to fade away over months. In 10 eyes, it was visible at presentation and in five eyes it could only be seen after clearing of the hemorrhage. Conclusion: Retinal yellowish-white arc ("arcus retinalis") is a useful clinical marker of sub-ILM hemorrhage with distinct OCT features that tends to disappear with time.